A Self‐Healing Metal–Organic Hydrogel for an All‐Solid Flexible Supercapacitor. Issue 65 (24th October 2019) - Karan, Chandan Kumar; Mallick, Sourav; Raj, C. Retna; Bhattacharjee, Manish
Abstract: A zinc containing metal–organic gel (Zn‐MOG) with embedded free ions, which exhibits self‐healing properties, has been synthesized for application in supercapacitors. The activated carbon‐based flexible supercapacitor device with the MOG electrolyte has a broad potential window of 2.1 V, with high retention of specific capacitance compared to the traditional polyvinyl alcohol (PVA)‐based gel. The Zn‐MOG does not require an additional electrolyte. The sodium and sulphate ions embedded in the MOG are sufficient enough for the charge storage. Abstract : A solid‐state supercapacitor has been fabricated by using a metal–organic hydrogel as the gel electrolyte, containing free sodium and sulphate ions embedded in the gel.